Evaluation as a as a tool for research, learning and making things better (Cambridge Scholars Publishing, 2014)
This book is one of the first of its kind to bring together a variety of perspectives on evaluation from a multidisciplinary international perspective. The book, with its content derived from leading experts in their chosen fields of practice, illustrates the potential of evaluation to demonstrate the impact and efficiency of social interventions. Examples are given of comparative effectiveness research, realist evaluation, and systematic reviews, as well as of holistic and authentic evaluati ...